MicroRNA-375 exacerbates knee osteoarthritis through repressing chondrocyte autophagy by targeting ATG2B - Li, Hongxing (Aging (Albany NY), 2020)
Objective: This study aimed to explore the underlying mechanism of miR-375 in exacerbating osteoarthritis (OA). Results: MiR-375 expression were upregulated in OA cartilage tissues, whereas ATG2B expression was decreased. MiR-375 targeted ATG2B 3’ UTR and inhibited its expression in the chondrocytes, and then suppressed autophagy and promoted endoplasmic reticulum stress (ERs). The apoptosis rate of chondrocytes was increased after being transfected with miR-375 mimics. In vivo results further verified that inhibition of miR-375 could relieve OA-related symptoms. Conclusion: miR-375 can inhibit the expression of ATG2B in chondrocytes, suppress autophagy and promote the ERs. It suggests that miR-375 could be considered to be a key therapy target for OA. Methods: Differential expression analyses for mRNA and miRNA microarray datasets from ArrayExpress were performed. MiR-375 and ATG2B expressions in cartilage tissues were detected by qRT-PCR. Dual luciferase assay was applied to verify the targeting relationship between ATG2B and miR-375. In vitro, the role of miR-375 on chondrocyte autophagy and ERs was investigated by western blot and immunofluorescence. The apoptotic rate was quantified by flow cytometry. In vivo, OA mice model was established, HE and Safranin O and Fast Green staining, as well as the OARSI and modified Mankin scores, were applied to measure the OA cartilage damage severity.